2020
DOI: 10.1111/apa.15155
|View full text |Cite
|
Sign up to set email alerts
|

Cystic fibrosis in the year 2020: A disease with a new face

Abstract: Abbreviations: CF, cystic fibrosis; CFTR, cystic fibrosis transmembrane conductance regulator; FEV 1 , forced expiratory volume in one second. AbstractThe autosomal recessive disease cystic fibrosis (CF) was once untreatable and deadly in childhood, but now most patients survive to adulthood. Many countries have insti-

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
183
0
15

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 232 publications
(200 citation statements)
references
References 53 publications
2
183
0
15
Order By: Relevance
“…It was quickly learned with IRT/DNA(CFTR) that the vast majority of CF cases can be presumptively (genetically) diagnosed within a week of birth from the initial blood specimen and valuable genetic data obtained to predict pancreatic functional status [33]. Later, the rapid genotyping capability of IRT/DNA (CFTR) screening also provided guidance for selection of CFTR modulators which can now be used to achieve organ preservation if begun early [34]. On the other hand, the CFTR multi-mutation tactic increases the number of incidental findings, particularly detection of CF heterozygote carriers, an increasingly important topic that is discussed in detail subsequently, and identification of those with CRMS/CFSPID (cystic fibrosis transmembrane conductance regulator-related metabolic syndrome/cystic fibrosis screen positive, inconclusive diagnosis) [35,36], which is well reviewed elsewhere [37] and beyond the scope of this article.…”
Section: Improvements In Irt/dna Screening Protocolsmentioning
confidence: 99%
See 1 more Smart Citation
“…It was quickly learned with IRT/DNA(CFTR) that the vast majority of CF cases can be presumptively (genetically) diagnosed within a week of birth from the initial blood specimen and valuable genetic data obtained to predict pancreatic functional status [33]. Later, the rapid genotyping capability of IRT/DNA (CFTR) screening also provided guidance for selection of CFTR modulators which can now be used to achieve organ preservation if begun early [34]. On the other hand, the CFTR multi-mutation tactic increases the number of incidental findings, particularly detection of CF heterozygote carriers, an increasingly important topic that is discussed in detail subsequently, and identification of those with CRMS/CFSPID (cystic fibrosis transmembrane conductance regulator-related metabolic syndrome/cystic fibrosis screen positive, inconclusive diagnosis) [35,36], which is well reviewed elsewhere [37] and beyond the scope of this article.…”
Section: Improvements In Irt/dna Screening Protocolsmentioning
confidence: 99%
“…Pancreatic insufficiency and its sequelae (risk of malnutrition, recurrent pancreatitis, and diabetes mellitus) have always been considered a permanent component of CF for the majority of patients with susceptible genotypes. To most CF specialists' surprise, however, CFTR modulator therapy has been associated with at least partial preservation of pancreatic function in recent studies examining this issue [34,[84][85][86]. In fact, the weight gains of CF patients in the original trials of ivacaftor suggested its potential to reduce the detrimental impact of pancreatic insufficiency [28], and subsequent observations support this hypothesis [87][88][89].…”
Section: The Opportunities For Preventive Therapiesmentioning
confidence: 99%
“…Cystic fibrosis (CF) was once untreatable and deadly in childhood, but most patients now survive to adulthood. A review by De Boeck 5 provides a general update on CF, including screening and current and future treatment. It shows that CF research has greatly intensified following the discovery of the CF transmembrane conductance regulator (CFTR) gene, which has more than 2000 different mutations.…”
Section: Cystic Fibrosis Is a Disease With A New Face In The Year 2020mentioning
confidence: 99%
“…Standard of care includes monitoring pulmonary function, nutritional status, airway clearance, and infection control [1]. Newer oral agents that are based on specific mutations are providing physicians with the ability to target underlying CFTR gene defects, thus leading to an increased life expectancy over 50 years [2] in patients with CF.…”
Section: Introductionmentioning
confidence: 99%